Economic valuation of a regional conservation program of marine turtles a contingent valuation survey of Iloilo City residents (in Southeast Asian perspective) - Deposoy, Janice Jatico
This study was conducted to determine the willingness to pay of Iloilo City Residents on a proposed regional conservation of marine turtles in Southeast Asia which will involve four countries: China, Thailand, Vietnam and Philippines. It also aimed at determining the factors that affect the willingness to pay of the respondents. a drop-off / self-adminstered questionnaire used for the survey. A total of 300 questionnaires were distributed in 12 selected barangays of Iloilo City but there were only 206 which were considered for encoding and analysis., Results show that the mean WTP of the Iloilo City residents for the proposed conservation of marine turtles is Php 26.8365 using the Turnbull section. The conservation value and the social mean WTP are Php 147, 493.404 and Php 19, 380, 078.357 respectively. The respondents in this survey were mostly female, Roman Catholics and reached at least high school level. The average income of those who answered is Php 10, 481.48. With regards to the level of awareness of the respondents on national issues and issues about the environment, it turned out that people view economic problems, poverty and government and their governance are the main problems that the government is facing right now. Most of the respondents did not believe that our natural environment is properly protected. Regarding issues on the effects of human activities on the natural environment, garbage disposal, forest degradation and air pollution are the dominant answers. The only factor that significantly affects in the WTP of the respondents is the belief of the respondents in the current situation of marine turtles. All other varaibles were not significant. The proposal of a surcharge in the payment of community tax certificate or cedula is not an acceptable mode of payment for the respondents.